Cover Picture: A Fully Integrated Continuous‐Flow System for Asymmetric Catalysis: Enantioselective Hydrogenation with Supported Ionic Liquid Phase Catalysts Using Supercritical CO2 as the Mobile Phase (Chem. Eur. J. 14/2013). Issue 14 (20th March 2013) - Hintermair, Ulrich; Franciò, Giancarlo; Leitner, Walter
<x xml:space="preserve">Abstract</x> Πάντα ρει (everything flows) Asymmetric catalytic transformation of low‐volatility organic substrates at mild reaction temperatures is achieved through a continuous‐flow process based on a chiral transition‐metal complex in a supported ionic‐liquid phase (SILP) with supercritical carbon dioxide (scCO2) as the mobile phase. In the contribution on page 4538 ff., W. Leitner et al. show how effective systems based on this principle can be developed in an integrated approach ranging from the molecular scale (catalyst structure), through the meso‐scale (separation strategy) to the macro‐scale (process scheme). (Illustration: www.luenenschloss‐design.de).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>